Performance evaluation of metakaolin as low cost adsorbent for manganese removal in anoxic groundwater - Mohd Sapingi, Mohd Sharizal; Murshed, Mohamad Fared; Tajaruddin, Husnul Azan; Mohd Omar, Fatehah (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The recent climate condition and pollution problem related to surface water have led to water scarcity in Malaysia. Huge amount of groundwater has been identified as viable source for drinking water.
Keywords: groundwater treatment; manganese removal; metakaolin; oczyszczanie wód gruntowych; usuwanie manganu